Quality Analysis Of Tomato Dodol Produced From Rice Flour Substitution - Febri Ananda; Rahmi Holinesti (Universitas Negeri Padang, 2021)
Dodol is a fairly popular traditional food that has been known since ancient times. Dodol is generally made from flour and fruit. Tomato dodol is one of the innovations of dodol made from fruit. This study aims to analyze the quality of tomato dodol substituted with rice flour with the ratio of glutinous rice flour and rice flour as much as 3:1, 1:1, and 1:3 in organoleptic tests on the shape, color, aroma, texture, and taste of tomato dodol. This type of research is a pure experiment using a completely randomized design (CRD) method, with three treatments and three repetitions. The data collection technique was carried out by giving questionnaires to 5 expert panelists who were lecturers of Family Welfare Science with the concentration of UNP Cuisine with primary data types. The data were analyzed using ANOVA, if Fcount Ftable then continued with Duncan's test. The results showed that there was a significant effect on the quality of the texture of the tomato dodol. The results of the quality test of tomato dodol with the best substitution of rice flour were in the third treatment (X2) with a ratio of 1:1 glutinous rice flour and rice flour.